2015
DOI: 10.3892/ol.2015.2946
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the effect of curcumin on the expression of p53 protein in a human multiple myeloma cell line

Abstract: Curcumin is an inexpensive, natural plant ingredient with protease inhibitor effects. The present study aimed to analyze the inhibitory effects of curcumin on the multiple myeloma (MM) RPMI 8226 cell line, and examine the underlying mechanism that promotes the apoptosis of RPMI 8226 cells. A growth curve was constructed in order to observe the relative growth velocity, and MTT was used to analyze the effect of different concentrations of curcumin on inhibiting the proliferation of the RPMI 8226 cells. The mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
(41 reference statements)
3
13
0
Order By: Relevance
“…Our finding indicated that treatment with curcumin-induced apoptosis of the tumor cells by the upregulation in the expression level of the P53 gene in HepG2 cells after administration of curcumin in a time-dependent manner. This result agrees with the previous studies that also reflected the role of curcumin in upregulating P53 protein expression in cancer cells of lymphoma-bearing mice [35], human multiple myeloma cell line RPMI 8226 cells [36] and vascular smooth muscle cell line, A7r5 [37].…”
Section: Discussionsupporting
confidence: 93%
“…Our finding indicated that treatment with curcumin-induced apoptosis of the tumor cells by the upregulation in the expression level of the P53 gene in HepG2 cells after administration of curcumin in a time-dependent manner. This result agrees with the previous studies that also reflected the role of curcumin in upregulating P53 protein expression in cancer cells of lymphoma-bearing mice [35], human multiple myeloma cell line RPMI 8226 cells [36] and vascular smooth muscle cell line, A7r5 [37].…”
Section: Discussionsupporting
confidence: 93%
“…It is reported that level of p53 in cells is controlled through many routes but major route is p53-murine double minute 2 (MDM2) pathway through an auto-regulatory feedback loop. Curcumin has shown downregulation of MDM2 leading to upregulation of the expression of p53 and Bax in multiple myeloma cancerous cells (Li et al, 2015). In conclusion, it is revealed that curcumin is effective for activation and restoration of p53 levels especially in the cells with an abnormal p53 expression or function.…”
Section: Epigenetic Modulation By Curcuminmentioning
confidence: 99%
“…The major features of carcinogenesis have been shown to be inhibited by curcumin 34 . Several mechanisms for anti-cancer activities of curcumin have been proposed, including, induction of apoptosis 34 , p53 stabilization 35 , mTOR 33 , Wnt 36 , Notch 37 , PI3K 38 , signaling inhibition, AMPK activation 39 , cell cycle inhibition 40 , inhibition of oncogenes 41 , inactivation of NF-kB 42 , metastasis inhibition 43 , angiogenesis inhibition 44 , miRNA regulation 45 , DNA damage and repair 46 . However, the effect of curcumin on cancer metabolism, an emerging hallmark of cancer, remains unknown.…”
Section: Introductionmentioning
confidence: 99%